2023
DOI: 10.1002/smll.202206318
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Silicon Matrix for Materials Engineering

Abstract: Tin‐containing layers with different degrees of oxidation are uniformly distributed along the length of silicon nanowires formed by a top‐down method by applying metalorganic chemical vapor deposition. The electronic and atomic structure of the obtained layers is investigated by applying nondestructive surface‐sensitive X‐ray absorption near edge spectroscopy using synchrotron radiation. The results demonstrated, for the first time, a distribution effect of the tin‐containing phases in the nanostructured silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Many studies have described the CVD process of Sn-based thin films using SnCl 4 and SnI 4 as the tin precursors. In our previous studies, we also presented the deposition of Sn/SnO 2 thin films using tin(IV) tertbutoxide as the tin and oxygen source [42,43]. This method is fast and simple for depositing Sn/SnO 2 thin films with a dense structure, and the morphology and composition can be easily changed by varying the deposition temperatures and substrates, as we showed previously [38].…”
Section: Vapor-based Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Many studies have described the CVD process of Sn-based thin films using SnCl 4 and SnI 4 as the tin precursors. In our previous studies, we also presented the deposition of Sn/SnO 2 thin films using tin(IV) tertbutoxide as the tin and oxygen source [42,43]. This method is fast and simple for depositing Sn/SnO 2 thin films with a dense structure, and the morphology and composition can be easily changed by varying the deposition temperatures and substrates, as we showed previously [38].…”
Section: Vapor-based Methodsmentioning
confidence: 88%
“…Chemical vapor deposition (CVD) has been widely used in the commercial deposi tion industry because of its inexpensive nature and flexibility in the production of synthe sis thin films and 1D nanostructures with high quality [38][39][40][41]. Many studies have de scribed the CVD process of Sn-based thin films using SnCl4 and SnI4 as the tin precursors In our previous studies, we also presented the deposition of Sn/SnO2 thin films using tin(IV) tert-butoxide as the tin and oxygen source [42,43]. This method is fast and simple (3) co-reactant process; (4) purge process [36].…”
Section: Vapor-based Methodsmentioning
confidence: 99%
“…A detailed explanation of the new tin phase separation effect in silicon nanochannels is discussed in our latest publication. [ 32 ] A significant extension to the standard characterization results achieved via SEM and XRD for the SnO 2 –SiNWs composite array provides the precise information on the surface atomic and electronic structures. The role of the surface is evident because the SEM image (Figure 1a) showed that the surface of SiNWs is covered by a flat layer containing tiny grains, presumably of tin oxides and possibly with metallic tin, as suggested from XRD (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Tin oxide thin films were deposited using a horizontal cold-wall reactor. [32,39] The substrates were heated by the inductive coupling of radiofrequency. Tin(IV) tert-butoxide (Sn(O t Bu) 4 ) [32,40] was used as a tin (Sn) and oxygen source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation